Iridocytes Mediate Photonic Cooperation Between Giant Clams (Tridacninae) and Their Photosynthetic Symbionts - Rossbach, Susann; Subedi, Ram Chandra; Ng, Tien Khee; Ooi, Boon S.; Duarte, Carlos M. (Frontiers in Marine Science, 2020)
Iridocytes, containing multiple stacks of proteinaceous platelets and crystalized guanine, alternating with thin cytoplasm sheets, are specialized cells that act as multilayer nano-reflectors. Convergence evolution led to their arising across a broad range of organisms, including giant clams of the Tridacninae subfamily - the only sessile and photosymbiotic organism, among animals known to possess iridocytes. Through the interference of light with their nanoscale architecture, iridocytes generate ‘structural colors’, which are reported to serve different purposes, from intra-species communication to camouflage. In giant clams, iridocytes were previously reported to promote a lateral - and forward scattering of photosynthetically productive radiation (PAR) into the clam tissue, as well as the back reflection of non-productive wavelengths. Hence, they are assumed to promote an increased efficiency in the use of available solar energy, while simultaneously preventing photodamage of the algal symbionts. We report the use of guanine crystals within Tridacna maxima giant clam iridocytes as a basis for photonic cooperation between the bivalve host and their photosynthetic symbionts. Our results suggest that, in addition to the previously described scattering processes, iridocytes absorb potentially damaging UV radiation (UVR) and, through successive emission, emit light at longer wavelengths, which is then absorbed by the photosynthetic pigments of the algal symbionts. Consequently, both, host and algal symbionts are sheltered from (potentially) damaging UVR, while the available solar energy within the PAR spectrum increases, thereby potentially enhancing photosynthetic and calcification rates in this large bivalve. Further, our results suggest that this photonic cooperation could be responsible for the broad repertoire of colors that characterizes the highly diverse mantle patterns found in T. maxima.